Toll-like receptor 4 deficiency in mice impairs venous thrombus resolution - Yuan, Haixin; Huang, Xiaoxi; Ding, Jie (Frontiers in Molecular Biosciences, 2023)
Objective: Toll-like receptor 4 (TLR4) is crucial to the development of sterile inflammatory responses. The deep venous thrombosis resolution (DVT) is similar to sterile inflammation, so we hypothesize that TLR4 is involved. Methods and Results: We evaluated the effects of TLR4 deficiency on thrombus lysis in vivo, and explored the mechanisms in vitro. DVT mouse model was established by inferior vena cava (IVC) ligation. After the IVC ligation (1, 3, and 7 d), the mice were euthanized to collect the venous thrombus. The Tlr4−/− mice had significantly elevated weight/length ratios of thrombi at 3 and 7 d and increased collagen content at 3 d after IVC ligation, in addition to significantly lesser intrathrombus infiltration of neutrophils and macrophages, lower monocyte chemoattractant protein-1 (MCP-1) and matrix metalloproteinase-9 (MMP-9) expression in thrombus tissue sections and homogenates, and lower pro-MMP-9 activity at 3 d after IVC ligation than wild-type mice. After 7 days of IVC ligation, VEGF, IFNβ, and MCP-5 protein expression were decreased in venous thrombus from Tlr4−/− mice. 2 ml of 3% thioglycolate was injected intraperitoneally and peritoneal exudate was collected 3 days later from Tlr4−/− and wild type mice respectively. The intraperitoneal macrophages were isolated from adherent culture after centrifugation. Lipopolysaccharide (LPS) can activate TLR4/NF-κB signalling pathway in a concentration-dependent manner, initiated p65 nuclear translocation, IκBα phosphorylation and degradation, MMP-9 and MCP-1 transcription in WT intraperitoneal macrophages but not in Tlr4−/− intraperitoneal macrophages. Conclusion: TLR4 is involved in venous thrombosis resolution through NF-κB pathway. Loss of TLR4 in mice impairs the process.